Evaluation of User Satisfaction in Relation to Comfort Conditions in Shopping Malls: Bursa as a Case - Filiz ŞENKAL SEZER; Tülin VURAL ARSLAN; Arzu ÇAHANTİMUR (Uludağ University Journal of The Faculty of Engineering, 2014)
Enclosed shopping malls are one of the most preferred spaces in our daily lives. In these places, visual and climatic comfort conditions of the users are generally provided by artificial systems instead of natural ones. In order to provide user satisfaction which is one of the most important requirements for the viability of these centers, the usage of these artificial systems causes higher energy consumption. In this study, it is argued that spatial organization scheme of shopping malls affects the subjective thoughts of the users’ interior comfort conditions (thermal, interior space air quality, natural ventilation, day lighting, audial comfort). In this context, 7 large shopping malls in Bursa were selected as case studies and the questionnaire aiming to evaluate the users’ satisfaction about comfort conditions in these shopping malls was carried out. The aim of the study is to identify the effects of architectural design principles and spatial organization schemes on the users’ evaluation of comfort conditions. The results of the questionnaire are classified under subtitles such as interior heat, thermal comfort, interior air quality and natural ventilation, day lighting, audial comfort .In this context, at the end of the study, the relation between the users’ subjective evaluation of comfort conditions and architectural design principles are comparatively discussed and some suggestions for the design of new shopping malls are provided